2012
DOI: 10.1136/jnnp-2012-303808
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid amyloid-  and phenotypic heterogeneity in de novo Parkinson's disease

Abstract: Motor heterogeneity in de novo PD independently relates to CSF Aβ markers, with low levels found in patients with the PIGD presentation. This suggests that disturbed Aβ metabolism has an effect on PD beyond cognition and may contribute to the variable rate of motor and functional decline in PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 45 publications
4
33
3
1
Order By: Relevance
“…Several studies have classified newly diagnosed/ untreated PD patients, or relatively mildly affected [32] into subtypes demonstrating heterogeneity in early PD [2,29,36]. This may work for ''early patients'', however, our findings indicate that categorization may be distorted in the more advanced stages of the disease.…”
Section: Considerations In Regards To Classification Into Pigd and Tdcontrasting
confidence: 59%
“…Several studies have classified newly diagnosed/ untreated PD patients, or relatively mildly affected [32] into subtypes demonstrating heterogeneity in early PD [2,29,36]. This may work for ''early patients'', however, our findings indicate that categorization may be distorted in the more advanced stages of the disease.…”
Section: Considerations In Regards To Classification Into Pigd and Tdcontrasting
confidence: 59%
“…Our findings broadly concur with previous cross-sectional reports showing a relationship with amyloid (from CSF and PET imaging) and motor disturbance especially in the PIGD phenotype in early and advanced PD. 10,11,30 However, importantly, our findings highlight limitations of previous work and argue for a more selective investigation of gait impairment.…”
Section: Postural Controlmentioning
confidence: 37%
“…Crosssectional studies in early and advanced PD show an association between CSF biomarkers and postural instability and gait (PIGD) phenotype. 10,11 However, lack of quantitative gait analysisFrom the Institute of Neuroscience …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…CSF amyloid beta peptides are altered from the early phases of PD, 68,69 especially in patients with dementia. 70 Regarding α-syn, the majority of recent studies have shown decreased CSF levels in PD patients, as compared to controls, although this marker apparently cannot distinguish among different synucleopathies.…”
Section: Csf Biomarkersmentioning
confidence: 99%